ON THE SUMMABILITY OF THE DISCRETE HILBERT TRANSFORM - Rashid A. Aliev (Ural Mathematical Journal, 2018)
In this paper, we study the asymptotic behavior of the distribution function of the discrete Hilbert transform of  sequences from the class \(l_{1} \) and find a necessary condition and a sufficient condition for the summability of the discrete Hilbert transform of a sequence from the class \(l_{1} \).